Analiza porównawcza struktur koszyków dóbr i usług konsumpcyjnych w krajach Unii Europejskiej - Grześkowiak, Alicja; Stanimir, Agnieszka (Comparative Analysis of Structures of Baskets of Consumer Goods and Services in European Union Countries, 2006)
This study is focused on structures of baskets of consumer goods and services. The comparative analysis carried out for some chosen European countries revealed the existence of regional diversity of structures of baskets. Changes of structures between 1996 and 2005 are described in the second part of this paper.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (17); 2006; nr 1123, s. 145-155